The Effect of Snowball Throwing Learning Model on Learning Outcomes of Aqidah Akhlak in Madinatul Ulum Islamic Elementery School - Imrie Purwa Hidayah; Hilyah Ashoumi (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This research examines the Aqidah Akhlak learning process in the fifth grade of Madrasah Ibtidaiyah Madinatul Ulum Tembelang Jombang, which is still having difficulty in improving student learning outcomes. The main problem identified is the low enthusiasm of students and the use of conventional learning methods. To overcome this, a learning model is needed that can increase the enthusiasm for learning and understanding of students, one of which is the snowball throwing learning model. This study aims to determine the effect of snowball throwing learning model on Aqidah Akhlak learning outcomes on the material of infaq and sadaqah in the fifth grade of Madrasah Ibtidaiyah Madinatul Ulum Tembelang Jombang. This study used an experimental method with a